2019
DOI: 10.1002/ar.24147
|View full text |Cite
|
Sign up to set email alerts
|

The CD147‐HYALURONAN Axis in Cancer

Abstract: CD147 (basigin; EMMPRIN), hyaluronan, and hyaluronan receptors (e.g., CD44) are intimately involved in several phenomena that underlie malignancy. A major avenue whereby they influence tumor progression is most likely their role in the characteristics of cancer stem cells (CSCs), subpopulations of tumor cells that exhibit chemoresistance, invasiveness, and potent tumorigenicity. Both CD147 and hyaluronan have been strongly implicated in chemoresistance and invasiveness, and may be drivers of CSC characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 151 publications
0
16
0
Order By: Relevance
“…Expression levels of CD147 and MMPs are often increased in inflammatory processes and tumors and are associated with cancer progression [14]. Cancer stem cells characterized by high cell surface CD147 expression produce more hyaluronan, resulting in stabilization of lipid rafts, as well as reveal enhanced MMP and ABC drug transporter expression, resistance and survival [15]. Recent studies have shown that patients with severe asthma have high levels of MMP-9 in sputum [16], and influenza A virus infection increases CD147 expression in cells from asthmatics [17].…”
Section: Cd147 As a Target For Covid-19 Treatmentmentioning
confidence: 99%
“…Expression levels of CD147 and MMPs are often increased in inflammatory processes and tumors and are associated with cancer progression [14]. Cancer stem cells characterized by high cell surface CD147 expression produce more hyaluronan, resulting in stabilization of lipid rafts, as well as reveal enhanced MMP and ABC drug transporter expression, resistance and survival [15]. Recent studies have shown that patients with severe asthma have high levels of MMP-9 in sputum [16], and influenza A virus infection increases CD147 expression in cells from asthmatics [17].…”
Section: Cd147 As a Target For Covid-19 Treatmentmentioning
confidence: 99%
“…To date, characterized HA receptors include CD44 [ 56 ], RHAMM (HMMR) [ 23 ], LYVE1 [ 57 ], TLR2/4 [ 29 , 58 ], STAB2/HARE [ 59 ], and LAYN [ 49 ]. CD44, LYVE1, and STAB2/HARE bind to HA via link modules [ 56 , 60 ].…”
Section: The Hyaluronomementioning
confidence: 99%
“…High expression of CD44 in cancer cells is also associated with cancer stem cell (CSC) properties and is used as a CSC marker. CD44 + cancer cells show an increase in EMT and in invasion, correlated with poor prognosis ( 55 58 ).…”
Section: Ecm Composition and Its Evolutive Role During Cancer Progresmentioning
confidence: 99%